Implementación de herramientas tecnológicas interactivas y su efecto en la enseñanza de los estudiantes del sexto paralelo B de la Unidad Educativa Adolfo María Astudillo del cantón Babahoyo periodo 2021-2022 - Cruz Álvarez, Mariuxi del Carmen (2022)
This research arises from the need to know if the teacher has adequately used the interactive technological tools in the teaching of the students of the sixth parallel B of the Adolfo María Astudillo Educational Unit of the Babahoyo canton period 2021-2022. It should be noted that the objective of this research was to determine the incidence of the execution of interactive technological tools in the teaching of students, believing it convenient to carry it out in the Adolfo Maria Astudillo educational unit of the Babahoyo canton to the students of sixth parallel B. The methodology used in this work is descriptive and quantitative, this research was carried out virtually in the Adolfo María Astudillo Educational Unit of the Babahoyo canton, our study sample being the 39 students and the teacher of the sixth parallel B course, of which previously The pertinent observations were made, it should be noted that the results obtained were thanks to a survey of the students and the interview with the course teacher. The results of the investigation was that the course teacher has not taken advantage of the previous knowledge that the students have about the interactive technological tools, which has reduced the knowledge of the students, causing a prejudice in learning.